Фітомодульний кластер як структурний елемент інтер’єpу внутрішніх приміщень різного функціонального призначення - Буюн, Л.І.; Іванніков, Р.В.; Якимець, В.М.; Степаньков, Р.С.; Харитонова, І.П.; Кожокару, А.А. (Наука та інновації, 2020)
Вступ. Сьогодні людину оточують нові токсичні речовини, які супроводжують технічний прогрес, а тому
пошук нових способів очищення повітря набуває все більшої актуальності.
Проблематика. У сучасних умовах виникає гостра необхідність розробки методів фіторемедіації повітря
приміщень, в яких упродовж тривалого часу перебуває значна кількість людей — профілактично-
лікарняних закладів, аудиторій, військових казарм, житлових приміщень тощо.
Мета. Створення кластерних фіторемедіаційних модулів для оптимізації повітряного середовища
приміщень.
Матеріали й методи. Використано анатомо-морфологічні, фізіолого-біохімічні, мікробіологічні методи, методи світлової та скануючої електронної мікроскопії.
Результати. Здійснено відбір з колекції тропічних рослин Національного ботанічного саду імені М.М. Гришка рослин-біофільтрів, що вирізняються підвищеною здатністю до поглинання шкідливих
речовин з повітря. Визначено кількісні та якісні критерії будови листка та фотосинтетичного апарату,
що визначають цю здатність рослин. Здійснено біотехнологічні методи розмноження рослин для фітомодулів. Підібрано типи контейнерів із системою автополиву та субстрати з низькою часткою органічної речовини. Спроєктовано та виготовлено світлодіодні фітолампи, кількісні та якісні характеристики яких відповідають оптимуму фотосинтетичних процесів. Проведено скринінг антимікробної
активності фітомодулів за умов стаціонарних відділень ДНУ «Центр інноваційних медичних технологій
НАН України». Показано, що контамінація повітря Staphylococcus saprophyticus після двотижневої експозиції зменшилась удвічі. Introduction. To date, people are surrounded by new toxic substances accompanying the development of technological
progress, therefore the searching a new ways for amelioration of indoor air quality has acquired an increasing urgency.
Problem Statement. Nowadays, the development of methods for phytoremediation of indoor environment of premises,
especially those where congestion of a significant number of people for a long time takes place (treatment and preventive care
establishments, classrooms, military barracks or housing accommodations) is increasingly necessary.
Purpose. To create cluster of phytoremediation modules to be used for amelioration of indoor air quality.
Materials and Methods. The anatomical and morphological, physiological and biochemical, microbiological methods,
light and SE M microscopy methods were used in the work.
Results. The selection of plants as biofilters with high potency to absorb the harmful substances from indoor air within
the collection of tropical plants of Gryshko National Botanic Garden has been undertaken.
The quantitative and qualitative criteria of both the leaf structure and the photosynthetic apparatus, determining the
ability of plants to absorb pollutants, were assessed. Biotechnological methods of plant propagation, involved in phytounits
have been worked out. Different types of containers with an automatic watering system and substrata with low part of
organic substances have been proposed. Additionally, plant compositions were equipped by LE D lamps elaborated to provide
plants with optimal full spectrum for photosynthetic performance. The screening of antimicrobial activity of phytounits was
undertaken in the departments of the Center for Innovative Medical Technologies. It has been established that an air
contamination by Staphylococcus saprophyticus after two-week exposition was reduced by half.
Conclusions. Thus, phytomodules, including the plants species which are nontoxic, with high remediation ability and
tolerant to various abiotic factors have been provided to be introduced into indoor area of treatment and preventive care
establishments and closed deployment places of security forces units.